Elemental profiling reveals rhizosphere oxidation-mediated selective Fe exclusion mechanisms against Fe toxicity in rice in Madagascar - Toavintsoa Rajonandraina; Yoshiaki Ueda; Hanna Manwaring; Tovohery Rakotoson; Diarikanto Ny Avo Rafearivo; Takanori Okamoto; Tendro Radanielina; Andry Andriamananjara; Tantely Razafimbelo; Matthias Wissuwa; Guy J. D. Kirk (Plant and Soil, 2026)
Background and aims Iron (Fe) toxicity in lowland rice is caused by high Fe levels and mineral imbalances within plants. Thus, maintaining whole-plant mineral balance may be crucial for tolerance. However, there is limited evidence from field studies on elemental profiling that elucidates specific tolerance mechanisms. Here, we tested whether contrasting Fe tolerance mechanisms are associated with distinct patterns of nutrient uptake and distribution. Methods We conducted multi-season experiments in Fe-toxic fields in Madagascar using rice genotypes with contrasting tolerance mechanisms. Elemental profiling was conducted for different parts of shoot tissues. Belowground Fe dynamics were investigated by measuring Fe plaque formation on roots and rhizosphere Fe 2 ⁺ levels. Results During the vegetative stages, tolerant genotypes that maintain low shoot Fe concentrations (excluders) showed a 48% reduction in shoot Fe uptake compared to other genotypes, while the uptake of other nutrients was less affected. Tolerant genotypes showed distinct within-plant nutrient allocation patterns. Excluders maintained lower Fe 2 ⁺ concentrations in the rhizosphere soil solution, as well as high root:shoot Fe concentration ratios. A mathematical model of the effects of Fe oxidation on soil pH and cation exchange could explain the decreased uptakes of Fe and other cations by excluders. Conclusion Genotypes with different tolerance levels and mechanisms exhibited distinct elemental profiles throughout growth. Genotypes with the same tolerance strategy may rely on distinct physiological mechanisms. Excluders selectively excluded Fe compared to other elements likely mediated by rhizosphere Fe oxidation.

The influence of age and captivity on cardiac structure and function in rhesus macaques - T. G. Dawkins; B. A. Curry; A. Drane; V. N. Rivas; Y. Ueda; J. A. Stern; D. Philips; J. Negron-Del Valle; Lauren Brent; James Higham; Angelina Ruiz-Lambides; Noah Snyder-Mackler; et al. (GeroScience, 2026)

Requirement of Trichome Formation for the Growth-promoting Effects of Olivine for Enhanced Weathering in Arabidopsis thaliana - Minoru Ueda; Daisuke Todaka; Satoshi Takahashi; Junko Ishida; Maho Tanaka; Tokihiro Ikeda; Keiko Suzuki; Misako Miwa; Takeshi Uchiyama; Yasuhiro Ishimaru; Kazuhiro Sayama; Nobuyuki Uozumi; et al. (Journal of Plant Growth Regulation, 2026)
Enhanced rock weathering helps remove CO 2 from air and cools the Earth over geological time periods, while also promoting plant growth, but the molecular mechanism underlying enhanced plant growth is unclear. In this study, ionome and transcriptome analyses revealed the importance of trichome formation for the growth-promoting effects of olivine ground to enhance weathering. In Arabidopsis, the application of 10% (w/w) olivine improved plant growth (a 64.2% increase in leaf area) and caused a 24.7% increase in Mg accumulation determined by ICP-AES at 23 days after germination (DAG) under long-day (16 h light/8 h dark cycle) conditions. Elemental maps of olivine-treated plants at 10 DAG produced by micro-particle-induced x-ray emission showed that olivine significantly altered Mg, K, and S accumulation in trichomes on true leaves, suggesting that trichomes may be critical for olivine-induced growth. The growth of glabrous1 ( gl1-1 and gl1-4 ) mutants defective in trichome initiation was not promoted by olivine. A transcriptome analysis of shoots by RNA-seq from wild-type plants at 16 DAG indicated olivine suppressed biotic stress-responsive gene expression. Additionally, Zn homeostasis was disrupted by olivine in gl1 mutants, implying that decreased Zn availability may inhibit the positive effect of olivine on growth. Collectively, our data uncovered the importance of trichomes to the adaptation of plants to soils containing rock-powders for crop improvement and agricultural sustainability and suggest the possibility that applying olivine might modulate the growth–defense trade-off governed by ion homeostasis mediated through trichome development, leading to improved plant growth.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Establishment of B4-100 and B4-C4, clonal canine multiple myeloma cell lines and their application in generating monoclonal antibody-producing fully canine hybridomas - Mark J. Micallef; Kaori Torihama; Kohei Fujikake; Akiko Kumagai; Atsushi Tanaka; Tomoyuki Kawai; Kazunori Ueda; Gakuto Hayashi; Shoji Ogino; Toshihiro Tsukui; Kenichi Masuda (Veterinary Immunology and Immunopathology, 2025)

A Pyrazole Partially Induces Brassinosteroid-Related Gene Expression, Leading to Salt Stress Sensitivity - Minoru Ueda; Satoshi Takahashi; Junko Ishida; Ayumi Yamagami; Takeshi Nakano; Florian Pünner; Mai Akakabe; Yoshihiro Sohtome; Atsushi J. Nagano; Mikiko Sodeoka; Motoaki Seki (Journal of Plant Growth Regulation, 2025)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Dietary nitrate does not acutely enhance skeletal muscle blood flow and vasodilation in the lower limbs of older adults during single-limb exercise - William E. Hughes; Nicholas T. Kruse; Kenichi Ueda; Andrew J. Feider; Satoshi Hanada; Joshua M. Bock; Darren P. Casey (European Journal of Applied Physiology, 2020)

Enrichment and characterization of a bacterial mixture capable of utilizing C-mannosyl tryptophan as a carbon source - Tanim J. Hossain; Shino Manabe; Yukishige Ito; Toshiya Iida; Saori Kosono; Kenji Ueda; Akira Hosomi; Daishi Inoue; Tadashi Suzuki (Glycoconjugate Journal, 2018)

The behavioural homing response of adult chum salmon Oncorhynchus keta to amino‐acid profiles - E. Y. Chen; J. B. K. Leonard; H. Ueda (Journal of Fish Biology, 2017)
Adult chum salmon Oncorhynchus keta homing behaviour in a two‐choice test tank (Y‐maze) was monitored using a passive integrated transponder (PIT)‐tag system in response to river‐specific dissolved free amino‐acid ( DFAA ) profiles and revealed that the majority of O. keta showed a preference for artificial natal‐stream water and tended to stay in this maze arm for a longer period; natal‐stream water was chosen over a nearby tributary's water, but not when the O. keta were presented with a non‐tributary water. The results demonstrate the ability of O. keta to discriminate artificial stream waters containing natural levels of DFAA .

Hydrogeochemistry and quality of surface water and groundwater in the vicinity of Lake Monoun, West Cameroon: approach from multivariate statistical analysis and stable isotopic characterization - Brice T. Kamtchueng; Wilson Y. Fantong; Mengnjo J. Wirmvem; Rosine E. Tiodjio; Alain F. Takounjou; Jules R. Ndam Ngoupayou; Minoru Kusakabe; Jing Zhang; Takeshi Ohba; Gregory Tanyileke; Joseph V. Hell; Akira Ueda (Environmental Monitoring and Assessment, 2016)

Patterns of cell thickness oscillations during directional migration of Physarum polycephalum - Beatrice Rodiek; Seiji Takagi; Tetsuo Ueda; Marcus. J. B. Hauser (European Biophysics Journal, 2015)

Gourmand New Caledonian crows munch rare escargots by dropping - Keita D. Tanaka; Yuji Okahisa; Nozomu J. Sato; Jörn Theuerkauf; Keisuke Ueda (Journal of Ethology, 2013)

Magma discharge variations during the 2011 eruptions of Shinmoe-dake volcano, Japan, revealed by geodetic and satellite observations - Tomofumi Kozono; Hideki Ueda; Taku Ozawa; Takehiro Koyaguchi; Eisuke Fujita; Akihiko Tomiya; Yujiro J Suzuki (Bulletin of Volcanology, 2013)

Differential Effect of Scaffold Shape on Dentin Regeneration - Akiko Tonomura; Daiki Mizuno; Akiko Hisada; Norihito Kuno; Yusuke Ando; Yoshinori Sumita; Masaki J. Honda; Kazuhito Satomura; Hiroya Sakurai; Minoru Ueda; Hideaki Kagami (Annals of Biomedical Engineering, 2010)

A virus and its vector, pepper yellow leaf curl virus and Bemisia tabaci, two new invaders of Indonesia - Paul J. De Barro; Sri Hendrastuti Hidayat; Don Frohlich; Siti Subandiyah; Shigenori Ueda (Biological Invasions, 2008)

Collagen type I matrix affects molecular and cellular behavior of purified porcine dental follicle cells - S. Tsuchiya; M. J. Honda; Y. Shinohara; M. Saito; M. Ueda (Cell and Tissue Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Bovine and water buffalo Mx2 genes: polymorphism and antiviral activity - H. A. E. Babiker; Y. Nakatsu; K. Yamada; A. Yoneda; A. Takada; J. Ueda; H. Hata; T. Watanabe (Immunogenetics, 2006)

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

First report of the Q biotype ofBemisia tabaci in Japan by mitochondrial cytochrome oxidase I sequence analysis - S. Ueda; J. K. Brown (Phytoparasitica, 2006)

Effects of an Environmental Estrogen on Male Gulf Pipefish, Syngnathus scovelli (Evermann and Kendall), a Male Brooding Teleost - N. Ueda; C. Partridge; J. Bolland; J. Hemming; T. Sherman; A. Boettcher (Bulletin of Environmental Contamination and Toxicology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Detection of Japanese yam mosaic virus by RT-LAMP - S. Fukuta; T. Iida; Y. Mizukami; A. Ishida; J. Ueda; M. Kanbe; Y. Ishimoto (Archives of Virology, 2003)

Molecular regulation of glutamate and GABA transporter proteins by valproic acid in rat hippocampus during epileptogenesis - Yuto Ueda; L. J. Willmore (Experimental Brain Research, 2000)

Polychlorinated Dibenzo- p -Dioxins (PCDDs), Dibenzofurans (PCDFs), Biphenyls (PCBs), and Organochlorine Pesticides in Yellow-Blotched Map Turtle from the Pascagoula River Basin, Mississippi, USA - K. Kannan; M. Ueda; J. A. Shelby; M. T. Mendonca; M. Kawano; M. Matsuda; T. Wakimoto; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2000)

Analysis of 5′-upstream non-coding region of FI-carboxymethyl cellulase gene from Aspergillus aculeatus - T. Ooi; K. Morotomi; S. Kinoshita; J. Honda; S. Ueda; M. Arai (Biotechnology Letters, 1999)

Uptake of 26-Al and 67-Ga into brain and other tissues of normal and hypotransferrinaemic mice - Aleksandar Radunovic´; Fukiko Ueda; Kishor B. Raja; Robert J. Simpson; Jill Templar; Samantha J. King; John S. Lilley; J. Philip Day; Michael W.B. Bradbury (BioMetals, 1997)

Provocation of respiratory allergy in guinea pigs following inhalation of free toluene diisocyanate - K. Aoyama; J. Huang; A. Ueda; T. Matsushita (Archives of Environmental Contamination and Toxicology, 1994)